3D Virtual Prototyping of Garments: Approaches, Developments and Challenges (Journal of Fiber Bioengineering and Informatics, 2018)
The paper deals with the 3D virtual prototyping of garments since they represent an important tool forbooth textile and garment designers. It offers simple introduction of changes while developing a model incomparison to conventional techniques, quick response to the costumer's demands and wishes regardlessof their location. Moreover, 3D virtual prototyping of garments can successfully replace prototypingprocesses when the specific garments are designed e.g. garments for people with the non-standard bodyfigure, wheelchair users, sportswear etc. The advantages and disadvantages of virtual prototyping ofgarments, used processes and methods, as well as the suggestions for new research opportunities on thefield of virtual simulation of garments and textile materials are presented.
Keywords: 3D Virtual Prototyping; Ski-jumper Suit; Garments for People with Paraplegi